Analisis sistem SIRINDUNONA menggunakan metode UTAUT pada Dinas Penanaman Modal dan PTSP Kabupaten Jombang: Analisis sistem SIRINDUNONA menggunakan metode UTAUT pada Dinas Penanaman Modal dan PTSP Kabupaten Jombang - styowati, widiyah; Hernyka Satyareni, Diema; Sukma Anugrah, Chandra (AMIK, 2024)
The Sirindunona system is a web-based system which is the entry point for applicants who wish to apply for non-business permits in various fields. Several fields that can make permits using the system are the health sector, the education sector, the livestock sector and the publication sector. This research was conducted to analyze the factors that influence the acceptance and use of the Sirindunona system using the Unified Theory of Acceptance and Use of Technology (UTAUT) model with 4 independent variables and 2 dependent variables, namely performance expectations, business expectations, social factors, facilitating conditions. behavioral intentions and user behavior. This research was conducted on 75 respondents who used the Sirindunona system. The UTAUT model is used to determine the level of success in accepting the Sirindunona system so that it can be accepted by the community. The data processing method used is multiple linear regression using SmartPLS 3 software. Results. From processing this data, it was found that the variables performance expectations, business expectations, social factors and facilitating conditions had a correlation value of 0.842 with behavioral intentions, meaning that the independent and dependent variables in this study had a very strong